2018
DOI: 10.3892/or.2018.6873
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol suppresses malignant proliferation of mammary epithelial cells through inhibition of the ROS‑mediated PI3K/AKT signaling pathway

Abstract: Reactive oxygen species (ROS) cause oncogenic mutations through direct interaction with DNA. Carvedilol (CAR) exhibits antioxidative activity, and pre-clinical studies have identified that CAR may prevent malignant transformation in certain carcinogenic models. This suggests that CAR may be a potential agent in cancer prevention. In the present study, non-cancerous MCF-10A cells were used as a model to investigate the chemopreventive effect of CAR on benzo(a)pyrene (BaP)-induced cellular carcinogenesis. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Two pathways known to be involved in skin carcinogenesis are UV-induced CPD formation (a DNA damage marker) and PGE 2 production (an inflammatory marker). Previously, it has been reported that carvedilol reduced DNA damage [7,8] and inflammation [11]. However, the data in the JB6 P+ cells and the 3D skin culture ( Figures 3A and 5A) were not as robust as the data obtained in mice [7].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Two pathways known to be involved in skin carcinogenesis are UV-induced CPD formation (a DNA damage marker) and PGE 2 production (an inflammatory marker). Previously, it has been reported that carvedilol reduced DNA damage [7,8] and inflammation [11]. However, the data in the JB6 P+ cells and the 3D skin culture ( Figures 3A and 5A) were not as robust as the data obtained in mice [7].…”
Section: Discussionmentioning
confidence: 66%
“…Carvedilol is a receptor subtype non-selective β-blocker with α-AR blocking and antioxidant properties [3][4][5]. Recent data demonstrate that carvedilol prevents malignant transformation and carcinogenesis induced by epidermal growth factor (EGF), chemical carcinogens, and UV [6][7][8][9]. However, the cancer preventive mechanism for carvedilol remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of MECs within the mammary gland depends on their proliferation. The proteome dataset of BuMECs contained a large number of proteins associated with phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) (225 Proteins) 58 , mTOR (114 Proteins) 59 and nuclear factor-kappa β (NFK-β) (50 Proteins) 60 signalling pathways, which are reported to have a direct role in the proliferation of MECs. Synthesis and secretion of milk components are among the main functions of MECs.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the PI3K/Akt pathways occurs in FSS-exposed cancer cells [ 38 , 81 , 82 ]. ROS generated during FSS [ 28 , 29 , 31 , 43 ] may signal activation of the PI3K/Akt pathway in breast cancer [ 83 , 84 , 85 ]. Application of a low level of FSS (1.8 dyn/cm 2 ) to MDA-MB-231 breast cancer cells increased phosphorylation of the regulatory subunit of PI3K, p85, followed by phosphorylation of the Ser 473 site of Akt [ 38 ].…”
Section: Cell Signaling Pathways In Circulating Tumor Cellsmentioning
confidence: 99%